Z metodologii badań nad zasobem leksykalnym uczniów - z uwzględnieniem odbioru podręczników i lektur szkolnych = Methodology of Research on the Lexical Knowledge of Pupils - Polański, Edward (Zielona Góra: Lubuskie Towarzystwo Naukowe)
At first the author makes a short and critical review of vocabulary tests undertaken in the course of research on the lexical knowledge of children and young people. The author defines the principles of the test's construction and pays attention to those criteria of the test which may have a strong hold on their diagnostical value. Next the author outlines the methods of his own researches on the comprehension of text-books and school literature by the pupils (on the example of the fourth grade of an Elementary School) from the view point of contents of lexical knowledge and describes among others the way of taking advantage of parametricalessential tests.
Keywords: dydaktyka literatury; młodzież; uczniowie; badania; podręczniki